Specific TCR gene rearrangements in mycosis fungoides: does advanced clinical stage show a preference?. Issue 12 (31st August 2018) - Marks, Etan; Wang, Yanhua; Shi, Yang; Susa, Joseph; Jacobson, Mark; Goldstein, D Yitzchak
Abstract : Aims: The relationship between the presence of specific T-cell receptor (TCR) gene rearrangements and clinical stage in mycosis fungoides (MF) has not been studied. We analysed a cohort of patients with a diagnosis of MF to determine the different types of specific TCR gene rearrangements present and their relationship to disease stage. Methods: A retrospective chart review was used to select patients with a diagnosis of MF who had a skin biopsy and a positive TCR gene rearrangement study in either blood or tissue and at least 2 years of clinical follow-up. Results: 43 patients were identified and divided into two groups. The first group consisted of 23 patients with early stage disease (IA-IIA) that was either stable or went into partial or complete remission with minimal intervention. None of these patients advanced to late stage disease. The second group consisted of 20 patients who had either late stage disease at diagnosis or progressed to late stage disease at some point in time. In the first group, only 4/23 (17%) patients had a single TCR gene rearrangement in the Vɣ1–8 region. In contrast, the second group had 13/20 (65%) patients with a single TCR gene rearrangement in the Vɣ1–8 region (p=0.002). Conclusion: The presence of a single TCR gene rearrangement in the Vɣ1–8 region could possibly be related to a more advanced stage of MF. However, more comprehensive studies, such as next generation sequencing, with a larger cohort is necessary for a more definitive conclusion.